Early Trauma and Relationships among Recent Stress, Depressive Symptoms, Anxiety Symptoms, and Suicidal Ideation in Korean Women - Park, C. Hyung Keun (J Korean Med Sci, 2021)
BACKGROUND: Evidence continues to accumulate that the presence or absence of early trauma (ET) implies unique characteristics in the relationships between suicidal ideation and its risk factors. We examined the relationships among recent stress, depressive symptoms, anxiety symptoms, and suicidal ideation in Korean suicidal women with or without such a history. METHODS: Using data on suicidal adult females, 217 victims and 134 non-victims of ET, from the Korean Cohort for the Model Predicting a Suicide and Suicide-related Behavior, we performed structural equation modeling to investigate the contribution of recent stress, depressive symptoms, and anxiety symptoms on suicidal ideation within each group according to the presence or absence of a history of ET. RESULTS: Structural equation modeling with anxiety and depressive symptoms as potential mediators showed a good fit. Recent stress had a direct effect on both depressive symptoms and anxiety symptoms in both groups. Only anxiety symptoms for victims of ET (standardized regression weight, 0.281; P = 0.005) and depressive symptoms for non-victims of ET (standardized regression weight, 0.326; P = 0.003) were full mediators that increased suicidal ideation. Thus, stress contributed to suicidal ideation by increasing the level of anxiety and depressive symptoms for victims and non-victims, respectively. CONCLUSION: Tailored strategies to reduce suicidal ideation should be implemented according to group type, victims or non-victims of ET. Beyond educating suicidal women in stress-management techniques, it would be effective to decrease anxiety symptoms for those with a history of ET and decrease depressive symptoms for those without such a history.